Traditional Foods: The Reinvented Superfoods - Roy, Swarnendu; Nisha, Prakasan; Chakraborty, Rakhi; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
Traditional foods can be defined as foods that have been consumed for several generations by a specific community in a particular locality, region or country. Many of these plant- and animal-based foods have traditionally been consumed for generations in different corners of the world, without proper understanding or knowledge of their beneficial properties. Apart from the basic nutritional attributes provided by these foods, they contribute to the prevention of several diseases, including hypertension, hyperglycemia and gastrointestinal disorders. The way traditional foods are prepared also plays a key role in naturally preserving the therapeutic potential of the food ingredients. In the present age of globalization, where food habits and food preferences are constantly being challenged, the reinvention of the therapeutic potential of traditional foods can provide a viable alternative. Measures have been initiated to gain an understanding of the beneficial attributes of traditional foods. Traditional Foods: The Reinvented Superfoods focuses on the health benefits of traditional foods in the light of recent evidence. This book also presents a fundamental overview of food-based therapy and the traditional methods that contribute to the preservation of the nutraceutical properties of food ingredients. This text comprehensively presents the background, history and prospects of traditional foods for a broad range of readers, presenting a balanced understanding of the present knowledge and technical advances in the field of traditional foods. Readers will find photographs of all the major traditional foods, along with illustrative schemes and sketches highlighting their preparation and future commercialization strategies.
Traditional foods of the the world: Regional specificities and their impact on the health and nutrition of ethnic communities -- Food and Medicine: Defining the boundaries and prospects for the future -- Food therapy: Origin, history and future prospects -- Fermented foods for traditional healing against metabolic diseases -- Ethnomedicinal plants of the Himalaya: From food to medicine -- Prebiotics and Probiotics: Enriching the gut microbiota and applications in addressing gastro-intestinal diseases -- Underutilized fruits and vegetables: Source of nutrient-rich phytochemicals and future prospects -- Scope of wild and lesser-known mushrooms for human health -- Dietary and medicinal benefits of edible algae -- Ethnobotanical and ethnomedicinal knowledge of spices and condiments -- Functional Foods: History, scope and future prospects -- Young cereal grains: The emerging nutraceuticals -- Nutritional benefits of underutilized millets and orphan crops -- Pickling: The art to preserve and enrich the health benefits of raw food products -- Cooking methods and their implications in the preservation of food nutrients and health benefits -- Traditional fermented beverages and their health benefits -- Therapeutic benefits of tea and effect of tea processing on health -- Biofortification using nutritionally rich traditional foods: A new dimension in food security -- Traditional animal-based food products and their relevance in providing nutritional security -- Traditional foods for festivity: Linking food diversity with socio-cultural aspects -- Safety and functionality of traditional foods: Challenges and remedies.
Keywords: Food science; Food -- Safety measures; Food security; Food Science; Food Safety; Food Security